Extraction, Chemical Composition, Antioxidant, and Antibacterial Activities of Essential Oil Using Aerial Part of Artemisia indica - Jaishi, Dipak Raj; Ojha, Indra; Ojha, Siddha Raj; Pal, Pooja; Thalal, Bhawana; Chaudhary, Paras Nath (Journal of Nepal Chemical Society, 2025)
Artemisia indica is a significant medicinal plant which has crucial applications such as antioxidant and antibacterial. The main aim of this study is to evaluate antioxidant potential, antibacterial activity, and extraction of essential oil and GC-MS analysis of essential oil collected from aerial parts of A. indica. The ethanolic extract of this plant exhibit potent antioxidant potential which is 17.75 ± 0.38 µg/mL. The methanolic and ethanolic extract had excellent zone of inhibition which is 21 and 20 mm against E. coli. This zone of inhibition is nearly close to positive control (neomycin 28 mm). 39 phytoconstitunets were identified from the AID (A. indica collected from Dadeldhura), similarly, 37 compounds were indentified in AIK sample (A. indica collected from Kanchanpur). In AID sample, α- thujone is the major phytoconstituents whereas in AIK sample eucalyptol is the major phytoconstituents. 21 phytoconstituents are common in both the sample. The half maximal inhibitory concentration for AID sample is 23.15 ± 1.59 µg/mL which is very effective antioxidant potential as compare to essential oil of AIK sample. Similarly, AID sample has very significant zone of inhibition (16 mm) against S. aureus. This zone of inhibition of AID sample shows good antibacterial potential. Due to diverse range of biological activity of A. inidica, it could be be used for the development of new drugs or new medications.